THE EFFECT OF SPACE VOLUME ON FREE CONVECTION HEAT TRANSFER FOR ONGITUDINAL FINNED CYLINDER WITH DIFFERENT SLOPE NGLES (Journal of Engineering, 2011)
This study deals with free convection heat transfer for the outer surface of twocylinders of the shape of (Triangular & Rectangular fined cylinders with 8-fins),putted into two different spaces; small one with dimension of (Length=1.2m,height=1m, width=0.9m) and large one with dimension of (Length=3.6m, height =3m,width=2.7m). The experimental work was conducted with air as a heat transportmedium. These cylinders were fixed at different slope angles (0o, 30o, 60o and 90o).The heat fluxes were (279, 1012, 1958, 3005, 4419) W/m2, where heat transferred byconvection and radiation. In large space, the results show that the heat transfer fromthe triangular finned cylinder is maximum at a slope angle equals to 90o and isminimum at the slope of 0o angle whit the heat transferred from the triangular finnedcylinder is maximum at slop angle of 30o and minimum at the slop of angle 60o in thesmall space with following range of the Raleigh number (1.68*107-3.46*108).